2020
DOI: 10.3390/s20247353
|View full text |Cite
|
Sign up to set email alerts
|

An IoT and Fog Computing-Based Monitoring System for Cardiovascular Patients with Automatic ECG Classification Using Deep Neural Networks

Abstract: Telemedicine and all types of monitoring systems have proven to be a useful and low-cost tool with a high level of applicability in cardiology. The objective of this work is to present an IoT-based monitoring system for cardiovascular patients. The system sends the ECG signal to a Fog layer service by using the LoRa communication protocol. Also, it includes an AI algorithm based on deep learning for the detection of Atrial Fibrillation and other heart rhythms. The automatic detection of arrhythmias can be comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 54 publications
1
14
0
Order By: Relevance
“…When an abnormal heart rhythm is detected, the device connected to the wireless network will send an alarm signal and detected abnormal data to the cloud data center, and the hospital will provide timely assistance after obtaining the data. The conceived scenario is shown in Figure 12 [79]. This study verifies the practicability of MobileNet and confirms that the deep learning algorithm can run effectively on small embedded devices.…”
Section: Lightweight Algorithmsupporting
confidence: 60%
See 1 more Smart Citation
“…When an abnormal heart rhythm is detected, the device connected to the wireless network will send an alarm signal and detected abnormal data to the cloud data center, and the hospital will provide timely assistance after obtaining the data. The conceived scenario is shown in Figure 12 [79]. This study verifies the practicability of MobileNet and confirms that the deep learning algorithm can run effectively on small embedded devices.…”
Section: Lightweight Algorithmsupporting
confidence: 60%
“…ImageNet dataset is not much different from that of the VGG model, the number of parameters of MobileNet is much less than that of the VGG model, as shown in Table 4. The portable ECG detection equipment used in studies uses MobileNet as the backbone network, which can obtain the user's ECG in real time and has a high accuracy rate [79]. The system uses three-lead ECG monitoring equipment to collect ECG signals and uses the local system composed of raspberry pi and an Intel NCS2 coprocessor to embed algorithms for intelligent detection.…”
Section: Lightweight Algorithmmentioning
confidence: 99%
“…It would be a first step towards the IoMT (Internet of Medical Things) [ 45 ]. It is also important to address the topics of edge computing and fog computing [ 46 , 47 ] in order to improve latency in communications and to reduce bandwidth.…”
Section: Discussionmentioning
confidence: 99%
“…The system was evaluated via a use case of arrhythmia detection and the results showed that the system can achieve a high level of accuracy with low latency. In [24], the authors also presented a Fog-based health motoring system for cardiovascular diseases. The collected ECG signals were sent via LoRa to Fog-based LoRa gateways where Fog-AI having deep learning module for the detection of Atrial fibrillation and other heart rhythms.…”
Section: Related Workmentioning
confidence: 99%
“…integrate Cloud resources. The performance of our proposed approach is compared with two existing approaches, namely IoT-Cloud [45] and IoT-Fog [24]. The IoT-Cloud solution uses AWS to run the DL model for processing IoT-device generated ECG signals in Cloud, whereas the IoT-Fog prototype exploits a cluster of 3 Raspberry Pi devices having Intel Neural Compute Stick 2 (NCS 2) to conduct the same operation on the Fog.…”
Section: B Efficiency Of the Hybrid Fog-cloud Infrastructurementioning
confidence: 99%